Clustering Mikrokapsul Silika-Chlorhexidine 2% Menggunakan Kitosan dan Sodium Alginat - Denny Nurdin; Angga Hudaya; Bambang Sunendar (Jurnal Material Kedokteran Gigi, 2012)
Enterococcus faecalis is a leading cause of persistent bacterial infection of the root canal. These bacteria have the ability to invade dentinal tubule penetration making it difficult to eliminate root canal medications. Dentinal tubules are so small between 1-3μm. Microencapsulation of the root canal medicament with a size less than 1μm is expected to be the way out to solve this problem. In this study used sodium silicate as a precursor and chlorohexidine 2% as a root canal the encapsulated drug. The method used is the sol gel Stober process. Clustering using chitosan and alginate materials made to microencapsulation chlorhexidine 2% in higher numbers. The purpose of this study was to obtain silica microcapsules with chlorhexidine 2% of active compound which is less than 1 μm homogeneously with chlorhexidine 2% of the active compound is encapsulated in greater numbers. The results showed that the sequence and composition of the chitosan-alginate affects the formation of clusters, the best results obtained on the composition of the cluster formation of chitosan 2% as much as 6% volume and 0.5 M alginate 2% volume, with an average cluster size of 0.7 μm